Numerical Simulation Study of the Hydrodynamic Properties of a Floating Breakwater of Pontoons - Cheng Xiaofei; Li Shimin; Xie Wei; Xu Chenhan; Wang Junnan; Xu Tiaojian (Polish Maritime Research)
To address the issue of insufficient wave dissipation capacity in standard floating breakwaters consisting of pontoons, this research proposes a combined floating breakwater with T-block connections. AQWA software is used to conduct numerical simulation studies on the dissipation characteristics of waves, and the reliability of the results is confirmed by integrating them with tests of a physical model. It is found that the transmission coefficient of the combined floating breakwater increases with the wave period. When the incident wave period T<6 s, increasing the relative height of the T-block improves the wave dissipation performance; when T>6 s, the effect is weakened; and at T=8 s, the change in height is basically unaffected. Increasing the relative width of the T-block is more significant in terms of the enhancement of the wave dissipation performance, whereas the height of the incident wave has a smaller effect on the transmission coefficient, and the transmission coefficient tends to increase with the increase of the wave height only in the case where T=8 s. The height of the incident wave has little effect on the transmission coefficient. The transmission coefficient increases with the wave height only when T=8 s; when the wave period is small (e.g. 4 s), the effect of wave elimination is enhanced by increasing the draught depth, and the draught does not have a significant effect on the wave dissipation performance when T>6 s. Compared with a typical floating pontoon breakwater with a single- and double-row arrangement, the combined floating pontoon breakwater has a better effect in terms of dissipating the waves, and its advantage is significant for a period T≤6 s, with a 44% increase in the maximum wave abatement compared to a single-row arrangement. In addition, the free-motion response is analysed to clarify the effects of different factors on the transverse and pendulum motion. This study provides an important reference for the design and application of floating pontoon breakwaters.